Direct detection of quasar feedback via the Sunyaev–Zeldovich effect. (15th November 2018) - Lacy, Mark; Mason, Brian; Sarazin, Craig; Chatterjee, Suchetana; Nyland, Kristina; Kimball, Amy; Rocha, Graca; Rowe, Barnaby; Surace, Jason
ABSTRACT: The nature and energetics of feedback from thermal winds in quasars can be constrained via observations of the Sunyaev–Zeldovich Effect (SZE) induced by the bubble of thermal plasma blown into the intergalactic medium by the quasar wind. In this letter, we present evidence that we have made the first detection of such a bubble, associated with the hyperluminous quasar HE 0515-4414. The SZE detection is corroborated by the presence of extended emission line gas at the same position angle as the wind. Our detection appears on only one side of the quasar, consistent with the SZE signal arising from a combination of thermal and kinetic contributions. Estimates of the energy in the wind allow us to constrain the wind luminosity to the lower end of theoretical predictions, ∼0.01 per cent of the bolometric luminosity of the quasar. However, the age we estimate for the bubble, ∼0.1 Gyr, and the long cooling time, ∼0.6 Gyr, means that such bubbles may be effective at providing feedback between bursts of quasar activity.